BCC communication through RZ Bipolar D-QPSK Encoding and Decoding with Hybrid RF base and FPGA Implementation - Dr. S.Vijayalakshmi, Mr. Sakthivel Sankaran, Dr. M. Pallikonda Rajasekaran, Dr. V.Nagarajan and Dr. E.Sankaran (International Journal of Advanced Science and Technology, 2020)
As of now it is seen that many technological developments are happening in the world particularly in the bio-medical field. These developments are helping the human being for easier diagnosing, identification, altering and rectifying the diseases immediately. With this advancement of communications such us Body Channel Communication (BCC), the problem solving can be carried out by the doctors at the real time in spite of long distance between doctors and patients. The transmitting and receiving the data such as blood pressure, temperature, ECG and EMG etc., can be made without any error in the signal. By the conventional BCC mode of communication it is experienced that there is several unwanted signals such as jitter noise, distortion in signals due to different body postures and motions of human and also it affects the human freedom. In order to overcome all these difficulties, DQPSK modulation technique is proposed and utilized in this research and to achieve high speed data transfer with more accuracy. In this research, to effect long range BCC, body wearable devices to monitor blood pressure, temperature, ECG and EMG are used. The output signals from these sensors are transmitted through 4, 8, 16 DQPSK modulators. For the purpose of secured and reliable data, 16 DQPSK techniques are used to achieve proper encoding and decoding methods. Hence, the line coding method is implemented in this proposed work to achieve the resultant data will be of error free without any overlap of signals. In this novel line coding method, RZ-Bipolar procedure is used to get greater data communication even with less power consumption and less bandwidth. To end with this VHDL design work, it is synthesized using MAX10 Altera Quaratus FPGA to study the performance comparison of output parameters such as power, delay and area.